A Critical Review of Vanadhanyaka (Eryngium foetidum Linn.) (International Journal of Ayurveda and Pharma Research, 2025)
Over the centuries, classical Ayurvedic texts have documented a vast array of medicinal plants, categorizing them based on Rasa, Guna, Veerya, Vipaka, and Prabhava. However, several plants traditionally known to indigenous communities remain inadequately described in classical treatises. One such plant is Vanadhanyaka (Eryngium foetidum), native to Mexico and South America and now cultivated worldwide, particularly as a spice plant. It is an annual or perennial herb with a characteristic fragrance similar to Dhanyaka (Coriandrum sativum). Eryngium foetidum is reported to be rich in calcium, iron, carotene and riboflavin. Leaves are an excellent source of vitamin A, B2, B1 and C. Phytochemical analyses of the leaves have revealed the presence of flavonoids, polyphenolic compounds, saponins, phytosteroids, triterpenoids, alkaloids, tannins, anthraquinones, cardiac glycosides, and terpenes. The major constituent of its essential oil is eryngial (E-2-dodecenal). Its reported pharmacological actions include antibacterial, anthelmintic, antioxidant, analgesic, and antipyretic activities. Although scarcely mentioned in Ayurvedic literature, ethnobotanical surveys and regional traditional practices indicate that Vanadhanyaka possesses notable therapeutic potential. It is traditionally used in conditions such as burns, ear ache, fever, hypertension, constipation, asthma, worms, infertility, snake bites, abdominal pain, malaria and diarrhea. This study seeks to bridge the gap between traditional Ayurvedic knowledge and contemporary scientific understanding by exploring Vanadhanyaka with respect to its botanical identification, vernacular nomenclature, regional usage, phytochemical composition, therapeutic applications, and methods of cultivation and propagation.